The Preferential Impairment of Pupil Constriction Stimulated by Blue Light in Patients with Type 2 Diabetes without Autonomic Neuropathy - Fukashi Ishibashi; Rie Kojima; Miki Taniguchi; Aiko Kosaka; Harumi Uetake; Mitra Tavakoli (Journal of Diabetes Research)
The main aim of the present paper is to examine whether the pupillary light reflex (PLR) mediated by intrinsically photosensitive retinal ganglion cells (ipRGCs) is impaired in type 2 diabetic patients. One hundred and three diabetic patients without diabetic autonomic neuropathy (DAN) and 42 age-matched controls underwent a series of detailed neurological examinations. The patients were stratified into three groups: stage I, no neuropathy; stage II, asymptomatic neuropathy; stage III, symptomatic but without DAN. The PLR to 470 and 635 nm light at 20 cd/m2 was recorded. Small fiber neuropathy was assessed by corneal confocal microscopy and quantifying corneal nerve fiber (CNF) morphology. The 470 nm light induced a stronger and faster PLR than did 635 nm light in all subjects. The PLR to both lights was impaired equally across all of the diabetic subgroups. The postillumination pupil response (PIPR) after 470 nm light offset at ≥1.7 sec was attenuated in diabetic patients without differences between subgroups. Receiver operating characteristic analysis revealed that the PIPR mediated by ipRGCs in patients with stage II and stage III neuropathy was different from that of the control subjects. Clinical factors, nerve conduction velocity, and CNF measures were significantly correlated with PLR parameters with 470 nm light. PLR kinetics were more impaired by stimulation with blue light than with red light in diabetic patients without DAN.